Financial instability and exchange rate dynamics in an agent-based model - Rodrigues, Lucca Henrique Gustafson (2024)
Exchange rates can be an important source of financial and economic instability. The dissertation develops a novel demand-led agent-based model to understand the joint dynamics between firm-level foreign indebtedness and exchange rate movements. In particular, we study the balance sheet effect, understood as a foreign liabilities after an exchage rate shock, with potential negative consequences to economic activity. We find that the impact on the real economy will depend on the relative strength between the financial and trade channels, but we always observe the negative financial consequences.